2022
DOI: 10.3390/polym14112194
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fiber/PLA Recycled Composite

Abstract: Due exceptional properties such as its high-temperature resistance, mechanical characteristics, and relatively lower price, the demand for carbon fiber has been increasing over the past years. The widespread use of carbon-fiber-reinforced polymers or plastics (CFRP) has attracted many industries. However, on the other hand, the increasing demand for carbon fibers has created a waste recycling problem that must be overcome. In this context, increasing plastic waste from the new 3D printing technology has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 94 publications
1
13
0
Order By: Relevance
“…Furthermore, the use of 3D printing technology for the preparation of antimicrobial polymeric composites could enhance their characteristics and performance through the consistent extrusion process. Therefore, this technology may be helpful for further investigations and applications in the biomedical, food, space, and textile fields, as well as other science and technology applications like recycling of waste materials [ 112 , 113 , 114 ] and implementing nanotechnology for better performance [ 115 ]…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of 3D printing technology for the preparation of antimicrobial polymeric composites could enhance their characteristics and performance through the consistent extrusion process. Therefore, this technology may be helpful for further investigations and applications in the biomedical, food, space, and textile fields, as well as other science and technology applications like recycling of waste materials [ 112 , 113 , 114 ] and implementing nanotechnology for better performance [ 115 ]…”
Section: Discussionmentioning
confidence: 99%
“…The compressive strength exhibited by multi material is 64.6 MPa±1.5 MPa. According to the referred literature, the compressive strength observed in reinforced polylactic acid and neat polylactic acid are 60 MPa and 53.3 MPa [19, 20]. During the compression test, slenderness ratio of test specimen will influence compression strength greatly [21].…”
Section: Resultsmentioning
confidence: 99%
“…The research that combined carbon fiber waste with PLA as shown in Figure 1 was successfully applied. The specimen was printed in the form of a tensile test with 3D printing, the test results showed that using recycled carbon fiber could increase the tensile strength [ 33 ]. Besides improving material properties, synthetic fiber recycling must be cost-effective [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%